Kajian Pemetaan Komoditas Kelapa Sawit (Elaeis guineensis jacq.) Pada Skripsi, Tesis dan Disertasi IPB sampai tahun 2022 - Ratnaningsih; Himawan Deden; Lindawati (Perpustakaan IPB, 2022)
Introduction. This study aims to determine the number and distribution of thesis research, theses and dissertations of IPB students related to oil palm commodities from various aspects that include it. The mapping of this field of science is expected in the future to become important and useful information related to the development of oil palm research at IPB University. Research Method This research uses descriptive quantitative method. The population is all thesis, thesis and dissertation data for IPB students related to palm oil commodities until 2022, obtained from the IPB Repository. The data was tabulated using Microsoft Excel and the data processing of science and keyword maps was using VOSviewer.Research result. There are 2,346 researches on oil palm commodities, most of which are found in the Faculty of Agriculture with 39% and the distribution in the Agricultural Industrial Technology Study Program is 11% for theses and 30% for dissertations. Mapping the distribution of oil palm research keywords found popular keywords that are widely used related to